(untitled) (International Journal of Physiology, 2019)
To determine the relationship of smart phone addiction with depression and aggression scores. Materials & Method Cross sectional observational data was collected from 205 young adults in the age group 18–25 years who uses smartphone more than 6 months. Smartphone addiction was assessed using scale-SV questionnaire. Beck Depression Inventory is widely used self-rated instrument to assess depression. Buss-Perry Aggression Scale(BRAQ) is a 29 item self-report measure of subject’s present level of aggressiveness. Results Spearman correlation coefficients were used to evaluate the relationship among the different variables. Multiple linear regression was used to assess the relationship between mental health problems (depression, aggression) and smartphone addiction score, after controlling for the effects of confounders. From this data smartphone addiction emerged as an independent predictor for aggression & depression in young adults(P < 0.001). Conclusion In conclusion, smartphone addiction symptoms has a potential influence on the mental health factors (Depression & aggression) among young adults.